Gender Differences in Visuospatial Abilities and Complex Mathematical Problem Solving - Ramírez-Uclés, Isabel M.; Ramírez-Uclés, Rafael (Frontiers in Psychology, 2020)
Mathematical problem-solving and spatial visualisation are areas in which performance has been shown to vary with sex. This article describes the impact of gender on spatial relations measured in 331 secondary school students (202 males, 129 females), 145 (105 males, 40 females) of whom had been selected to participate in a mathematical talent stimulation project after passing a complex problem-solving test. In the two tests administered, the Differential Aptitude Tests-Space Relations (DAT-SR) and the Primary Mental Abilities-Space Relations (PMA-SR), performance was assessed on the grounds of both absolute scores and the ratio to the number of items answered. The students participating in the talent programme earned higher scores on both tests, although no interaction was identified between mathematical abilities and gender in connection with the differences in spatial habilities observed. In PMA-SR, boys answered more items and scored higher, whereas in DAT-SR girls tended to omit more items. None of the indicators studied exhibited differences between the sexes in both tests and in some cases the differences in the absolute values of the indicators were absent when expressed as ratios.